Significance of High-Mobility Group A Protein 2 Expression in Pancreatic Ductal Adenocarcinoma and Ampullary Adenocarcinoma - Oflas, Damla; Canaz, Funda; Özer, İlter; Demir, Lütfiye; Çolak, Ertuğrul (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Pancreatic and ampullary adenocarcinoma (AAC) are quite resistant to chemotherapy with high metastasis potential. Our study aimed to interpret high-mobility group A protein 2 (HMGA2) expression in benign and precursor pancreatic lesions and pancreatic and ampullary carcinoma and to evaluate its relationship with epithelial–mesenchymal transition (EMT) and clinicopathological parameters. Materials and Methods: In this study, normal-appearing pancreas, chronic pancreatitis (CP), low- (L) and high (H)-grade pancreatic intraepithelial neoplasia (PanIN), pancreatic ductal adenocarcinoma (PDAC), and AAC were evaluated with the immunohistochemical marker of HMGA2. Vimentin and E-cadherin immunohistochemical stains were applied in PDAC and AAC. Results: The HMGA2 expression was not detected in normal-appearing pancreas, CP, and L-PanIN. A statistically significant expression was observed in PDAC and H-PanIN (P < .001). A statistically significant correlation was found between loss of membranous E-cadherin expression and vimentin positivity and HMGA2 expression (P > .05). The HMGA2 expression was observed to increase the risk of diseaserelated death and decrease overall survival (OS) in AAC and the neoplasia group (P = .002 and P = .016, respectively). There was no significant difference in OS and risk of death in PDAC (P > .05) with respect to HMGA2 positivity. Conclusion: High-mobility group A protein 2 is a helpful immunohistochemical marker in differentiating CP from PDAC. It also plays a role in EMT and may serve as a potential new prognostic agent and therapeutic target in tumors of the periampullary region, especially AAC. Cite this article as: Oflas D, Canaz F, Özer İ, Demir L, Çolak E. Significance of high-mobility group A protein 2 protein expression in pancreatic ductal adenocarcinoma and ampullary adenocarcinoma. Turk J Gastroenterol. 2023;34(10):1014-1024.